2013
DOI: 10.1158/1078-0432.ccr-12-2043
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Clinical Relevance of miRNA Expression Signatures in Primary Plasma Cell Leukemia

Abstract: Purpose: Primary plasma cell leukemia (pPCL) is a rare and very aggressive form of plasma cell dyscrasia. To date, no information on microRNA (miRNA) expression in pPCL has been reported. This study aimed at investigating the involvement of miRNAs in pPCL and their possible relationship with higher tumor aggressiveness.Experimental design: Global miRNA expression profiles were analyzed in highly purified malignant plasma cells from 18 pPCL untreated patients included in a prospective clinical trial. MiRNA expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 50 publications
1
62
0
2
Order By: Relevance
“…Because we could not add to the results of FISH due to the lack of data, we would need to attempt a reanalysis of OS including the FISH results. Recent studies have shown new prognostic factors, including miRNA and gene expression profiles in pPCL, which correlated with treatment response and survival [29,30,31]. In the future, we need to incorporate these data in the prognostic analysis of pPCL.…”
Section: Discussionmentioning
confidence: 99%
“…Because we could not add to the results of FISH due to the lack of data, we would need to attempt a reanalysis of OS including the FISH results. Recent studies have shown new prognostic factors, including miRNA and gene expression profiles in pPCL, which correlated with treatment response and survival [29,30,31]. In the future, we need to incorporate these data in the prognostic analysis of pPCL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR-330-3p is up-regulated in the blood of patients with prostate cancer and primary plasma cell leukemia [20,21]. Recent studies have demonstrated that miR-330-3p expression was increased in NSCLC patient tissues, and miR-330-3p was also involved in NSCLC brain metastasis with 53-fold higher expression compared with non-metastasis NSCLC [22,23].…”
Section: Introductionmentioning
confidence: 97%
“…High expression of miR-22 can explain the lack of response in pemetrexed-treated non-small cell lung cancer (NSCLC) patients. However, in primary plasma cell leukemia, miR-22 is associated with a positive clinical outcome (35). One study suggested that circulating miR-431 can contribute to the detection of colorectal cancer (36).…”
Section: Discussionmentioning
confidence: 99%